PATHOMORPHOLOGICAL CHANGES OF THE PLACENTA IN THE ACUTE PERIOD OF COVID-19 IN PREGNANT WOMEN - Savchuk, Tetiana (Eastern Ukrainian Medical Journal, 2024)
Introduction. The barrier function of the mature placenta ensures the birth of PCR-negative infants in women during the acute period of coronavirus disease (COVID-19). This was explained by a decrease in the level of activity and concentration of angiotensin-converting enzyme type II protein (ACE2), which is a receptor for the coronavirus SARS-CoV-2 in the placenta. We conducted this study in order to detect compensatory changes in the placenta during COVID-19 in a pregnant woman. The aim of the study: To determine pathomorphological changes of the placenta in the acute period of COVID-19 in a pregnant woman. Materials and methods. The placentas of women with full-term pregnancy who were having COVID-19 confirmed by a positive PCR test (determination of SARS-CoV-2 RNA) during childbirth (n=32) were studied. The duration of the post-COVID interval (time from the diagnosis of COVID-19 to delivery) equaled 1–4 weeks. Macroscopic, organometric, microscopic, statistical, and immunohistochemical (with determination of CD34 monoclonal antibody expression) research methods were used. To determine the percentage of the studied structures that differed in color after histological staining, archival photos (×400) were uploaded to ONLINE JPG TOOLS. Results. Delivery dates: 37 to 42 weeks of gestation (median 40). COVID-19 occurred in the period 34 to 40 weeks of gestation (median 36). Course of coronavirus disease in pregnant women: 10 – mild, 18 – medium-severe, severe condition with bilateral polysegmental pneumonia – 4 women. Evaluation of newborns according to the Apgar score: 21 children (65.6%) – 8–9 points, 9 cases (28.1%) – 7–8 points, and one observation – 3–4 points and 6–7 points. No significant difference was found between the clinical manifestations of COVID-19 or the severity of the course of the disease in the pregnant woman and the morphological changes of the placenta. Microscopic examination of the placenta revealed placentitis: chorioamnionitis – 93.8% (95%CI: 82.4%–99.5%), basal deciduitis – 100% (95%CI: 94.2%–100%), villitis and intervillositis – 28.1% (95%CI: 13.7%–45.4%). The degree of manifestations of chorioamnionitis: (+) and (++) was in 34.4% (95% CI: 18.6%–52.1%), basal deciduitis (+) – 15.6% (95% CI: 5 %–30.6%), p1-2=0.08; and (++) in 28.1% (95% CI: 13.7%–45.4%). Manifestation of chorioamnionitis in (+++) and (++++) in 11.8% (95% CI: 3.2%–26.6%), basal deciduitis (+++) in 28.1% (95 % CI: 13.7%–45.4%) and (++++) in 15.6% (95% CI: 5%–30.6%). The expression of manifestations of basal deciduitis (+++++) was found in 11.8% (95% CI: 3.2%–26.6%), p1-2=0.04. The degree of severity of inflammatory changes of the maternal surface of the placenta from (+++) to (+++++) with minor similar changes in the amniotic membranes (+) and (++) confirmed the vertical route of infection. Edema of the stroma of the terminal villi was detected in 90.6% (95% CI: 77.7%–98.3%) and caused a narrowing of the lumen of the capillaries of the terminal villi of the chorion, and a decrease in the percentage of the intervillous space – 26.0 [20.7; 33.8] vs. 44.9 [40.5; 49.6] as a normal value; p = 0.0005. Percentages in a histological section of the terminal villus: stroma – 72.3 [65.8; 78.7], blood vessels – 29.0 [25.6; 34.2] vs. normal indicators: 32.1 [26.2; 39.6] and 67.8 [60.3; 73.7], respectively; p = 0.0039. Conclusions. Maternal pathomorphological changes in full-term pregnancy in the acute period of COVID-19 were caused by the exudation phase of the inflammatory process, which explained the manifestations of placentitis, swelling of the stroma of terminal villi with narrowing of the lumen of capillaries, dyscirculatory disorders. Live birth with high scores on the Apgar scale was ensured by compensatory changes of the mature placenta: an increase in the number of syncytial nodules, the locality of villitis and intervillositis, as mechanisms of increasing the intervillous space to ensure adequate perfusion.